The importance of time-varying parameters in new Keynesian models with zero lower bound - Julien Albertini; Hong Lan (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2016)
In this paper we question the ability of New Keynesian models to reproduce the behavior of the nominal interest rate. In particular, we wonder if the model is able to reproduce infrequent but long ZLB spells as observed in the data. Starting from the canonical model, we compare alternative specifications like exogenous and endogenous time-varying parameters. We solve the different models with global approximation methods and estimate them using the simulated method of moments. While the canonical model fails to reproduce typical ZLB spells, the endogenous time-varying parameters specification seems to be a promising avenue for research. We draw the implications of the alternative model's specifications for the understanding of the monetary policy during ZLB episodes.
Keywords: E3; J6; 330; New Keynesian model; ZLB; Time-varying parameters; Method of moments